Identifikasi Jenis dan Analisis Morfometrik Ordo Anura di Sungai Lau Timah, Sibolangit, Sumatera Utara - Rosifa, Gita Dewi; Hutasuhut, Melfa Aisyah; Idami, Zahratul (Universitas Medan Area, 2024)
Anura are amphibians capable of living in both terrestrial and aquatic habitats, yet they are highly sensitive to environmental changes. Some Anura species can adapt well, while others are more vulnerable to such changes. The Lau Timah River, located in Desa Bukum, Sibolangit, North Sumatra, is known for its high diversity of Anura species, supported by abundant water availability. This study aimed to identify Anura species and analyze their morphometric variations in the Lau Timah River. The research employed the Visual Encounter Survey (VES) method with three repetitions on different days. A total of 24 individuals were sampled, and 13 Anura species were identified, including Chalcorana chalconota, C. kampenii, C. rufipes, Odorrana hosii, Pulchrana siberu, Huia sumatrana, Limnonectes blythii, L. kuhlii, L. macrodon, Pelophryne signata, Letophryne borbonica, Ingeophrynus divergens, and Megophrys nasuta. The species were documented and measured for morphometric analysis. The analysis revealed significant morphometric differences in parameters such as PB, PM, LK, PK, PMTJ4, and PTJ4. The highest R² values were found in L. kuhlii, L. macrodon, I. divergens, and L. borbonica, indicating a very strong correlation.